The quality of perinatal care in the Cardinal Stefan Wyszyński Regional Hospital in Łomża - Roszkowska, Urszula; Kulesza-Brończyk, Bożena; Dobrzycka, Bożena; Terlikowski, Sławomir (Polish Journal of Public Health, 2009)
Introduction. Patient rights are an integral part of human rights in the broad sense of the word. The basis for these rights is acknowledging the unalienable right to dignity of every human, his/her autonomy and freedom in every situation, including specific relationship between a patient and medical stuff. The aim of the study. The aim of the study was to evaluate the quality of obstetric care and observing patient rights in the obstetric ward of the Cardinal Stefan Wyszyński Regional Hospital in Łomża. Material and method. The survey covered 200 randomly chosen women in labour. Results and discussion. Many positive examples of respecting patient rights among medical staff were observed. It is worth noticing that 90% of the women in labour were accompanied by a close person. Satisfactory information was obtained by 82% of the women about their and their children’s state of health. Over 40% of the patients obtained full information about the course of their labour. Ninety one per cent (91%) of the surveyed women agreed to medical intervention. High percentage of the women in labour (78%) could move freely and choose convenient labour positions. Conclusions. The Cardinal Stefan Wyszyński Regional Hospital in Łomża assures high standard of obstetric care based on the principles of the campaign for labour environment improvement (“Childbirth with Dignity”). Monitoring of patient rights observance has considerable infl uence on the quality of obstetric care in the hospital.